Development and use of a content search strategy for retrieving studies on patients' views and preferences - Anna Selva; Ivan Solà; Yuan Zhang; Hector Pardo-Hernandez; R. Brian Haynes; Laura Martínez García; Tamara Navarro; Holger Schünemann; Pablo Alonso-Coello (Health and Quality of Life Outcomes, 2017)
Abstract Background Identifying scientific literature addressing patients’ views and preferences is complex due to the wide range of studies that can be informative and the poor indexing of this evidence. Given the lack of guidance we developed a search strategy to retrieve this type of evidence. Methods We assembled an initial list of terms from several sources, including the revision of the terms and indexing of topic-related studies and, methods research literature, and other relevant projects and systematic reviews. We used the relative recall approach, evaluating the capacity of the designed search strategy for retrieving studies included in relevant systematic reviews for the topic. We implemented in practice the final version of the search strategy for conducting systematic reviews and guidelines, and calculated search’s precision and the number of references needed to read (NNR). Results We assembled an initial version of the search strategy, which had a relative recall of 87.4% (yield of 132/out of 151 studies). We then added some additional terms from the studies not initially identified, and re-tested this improved version against the studies included in a new set of systematic reviews, reaching a relative recall of 85.8% (151/out of 176 studies, 95% CI 79.9 to 90.2). This final version of the strategy includes two sets of terms related with two domains: “Patient Preferences and Decision Making” and “Health State Utilities Values”. When we used the search strategy for the development of systematic reviews and clinical guidelines we obtained low precision values (ranging from 2% to 5%), and the NNR from 20 to 50. Conclusions This search strategy fills an important research gap in this field. It will help systematic reviewers, clinical guideline developers, and policy-makers to retrieve published research on patients’ views and preferences. In turn, this will facilitate the inclusion of this critical aspect when formulating heath care decisions, including recommendations.